The Influence Of Social Media, Celebrity Endoser, And Brand Image On Consumer Purchase Decisions At Tokopedia - Agtovia Frimayasa; Ibnu Haris Nasution (CV. Ulil Albab Corp, 2022)
The purpose of this study was to determine the effect of Social Media, Celebrity Endorser and Brand Image on Consumer Purchase Decisions at Pedia Stores. The research approach used in this study is a quantitative approach with data processing using SEM PLS, with a sample of 80 respondents. The criteria for testing discriminant validity are based on the value of the test variable which is greater than the value of the other variables. Based on the test results, it is known that the values of the X1 and X2 variables are smaller than the two Y variables. Thus, the test results are not discriminantly valid. Cronbach's alpha value is more than 0.7, so it can indicate a value above 0.7. Thus, the data can be said to be valid. Based on these results, it can be seen that the value of the construct in question is always greater in the variable itself. Based on these results, it can be concluded that there is no discriminant validity problem. The results of the Cross Loading Factor show that each variable is > 0.7. Based on the table, the R-Square value for the satisfaction construct is 0.456, which means this value can identify y which can be explained by the x variable by 45.6%, while the rest is influenced by other variables outside the study. The results of this study indicate that social media has a significant positive effect on purchasing decisions. Celebrity endorsers have a significant positive effect on purchasing decisions. Brand Image has a significant positive effect on purchasing decisions.